A comparative investigation of gelatinized and regenerated starch composites reinforced by microfibrillated cellulose. (30th March 2022) - Tian, Yu; Zhou, Mi; Luo, Ting; Zhu, PuXin; Cheng, Fei; Zhang, Yong; Lin, Yi
Highlights: Starch was dissolved in 14 wt% urea/4 wt% NaOH solution at 0 °C and regenerated. Regenerated starch film showed good mechanical property. The addition of cellulose improved the mechanical property of starch. Abstract: This research demonstrated a novel and ecofriendly method for producing regenerated starch (RS)/microfibrillated cellulose (MFC) composite films with a nearly 1.4-fold improvement in tensile strength than traditional gelatinized starch (GS) films. Pure starch was dissolved in 14 wt% urea/4 wt% sodium hydroxide (NaOH) solution at 0 °C. Then, RS films and their biocomposite films containing MFC were prepared by dialyzing and solution-casting method. Results showed that the tensile strength and elongation at break of RS increased by 44.8% and 82.4%, compared with that of GS film, respectively. Owing to the adequate dispersion, lower viscosity-average molecular weight, higher amylose content, lower crystallinity and smaller crystal grain size, RS/MFC composite films exhibited significantly improved mechanical properties. The novel strategy used in this study will be helpful in preparing regenerated starch materials with excellent mechanical properties and biodegradability as alternatives to petrochemical plastics for the development of sustainable materials.